Spatiotemporal Analysis of Interaction of Pollutants on Pneumonia Cases Distribution in Metropolitan Jakarta - Salman Alfarisi; Syavera, Venita (Universitas Airlangga, 2025)
Introduction: Pneumonia is one of the leading causes of death in children under five globally, including in Indonesia. Large metropolitan cities such as Jakarta face a heavier burden due to poor air quality and high population density, further increasing the spread of this disease. This study aims to identify areas with high pneumonia risk and contributing pollutant factors to support more effective interventions and guide policy-making in reducing the impact of pneumonia in urban areas. Methods: This study used the Besag-York-Mollié 2 spatiotemporal model with INLA to analyze the geographic distribution of disease and the influence of pollutant factors. The data comes from Social Security Agency, which has not been used in previous similar studies, and the Jakarta Environmental Agency, thus providing a more accurate description of the actual conditions. Results and Discussion: The effects of pollutants were analyzed based on their credibility intervals, with CO (0.0004, 0.0014); SO2 (-0.0220, 0.0092); and PM10 (-0.0123, 0.0362). Meanwhile, the effect of the time factor (year) has a credibility interval of (0.1669, 0.3464). Spatiotemporal analysis shows an increase in relative risk spread across Jakarta. Conclusion: It was shown through the study that pollutants, particularly CO, positively affected the rising cases of pneumonia, whereas other pollutants discussed under the study had no significant impact. Additionally, time also made a significant impact on the study. The risk ratio for every region of Jakarta rose, and this highlights the importance of air quality management, sustainable urban development, and access to health in an equitable equally.